Increased PSA expression on prostate cancer exosomes in in vitro condition and in cancer patients - Logozzi, Mariantonia; Angelini, Daniela F.; Iessi, Elisabetta; Mizzoni, Davide; Di Raimo, Rossella; Federici, Cristina; Lugini, Luana; Borsellino, Giovanna; Gentilucci, Alessandro; Pierella, Federico; Marzio, Vittorio; Sciarra, Alessandro; et al. (Cancer letters, 2017)
Prostate specific antigen (PSA) test is the most common, clinically validated test for the diagnosis of prostate cancer (PCa). While neoplastic lesions of the prostate may cause aberrant levels of PSA in the blood, the quantitation of free or complexed PSA poorly discriminates cancer patients from those developing benign lesions, often leading to invasive and unnecessary surgical procedures. Microenvironmental acidity increases exosome release by cancer cells. In this study we evaluated whether acidity, a critical phenotype of malignancy, could influence exosome release and increase the PSA expression in nanovesicles released by PCa cells. To this aim, we exploited Nanoparticle Tracking Analysis (NTA), an immunocapture-based ELISA, and nanoscale flow-cytometry. The results show that microenvironmental acidity induces an increased release of nanovesicles expressing both PSA and the exosome marker CD81. In order to verify whether the changes induced by the local selective pressure of extracellular acidity may correspond to a clinical pathway we used the same approach to evaluate the levels of PSA-expressing exosomes in the plasma of PCa patients and controls, including subjects with benign prostatic hypertrophy (BPH). The results show that only PCa patients have high levels of nanovesicles expressing both CD81 and PSA. This study shows that tumor acidity exerts a selective pressure leading to the release of extracellular vesicles that express both PSA and exosome markers. A comparable scenario was shown in the plasma of prostate cancer patients as compared to both BPH and healthy controls. These results suggest that microenvironmental acidity may represent a key factor which determines qualitatively and quantitatively the release of extracellular vesicles by malignant tumors, including prostate cancer. This condition leads to the spill-over of nanovesicles into the peripheral blood of prostate cancer patients, where the levels of tumor biomarkers expressed by exosomes, such as PSA-exosomes, may represent a novel, non-invasive clinical tool for the screening and early diagnosis of prostate cancer. •PSA prostate-specific antigen (PSA) is a prostate cancer (PCa) specific marker.•Microenvironmental acidity increases exosome release by cancer cells.•Acidity induces expression of PSA by exosomes.•PCa patients had high levels of PSA-expressing exosomes.•Tumor acidity exerts a selective pressure leading to expression of PSA by exosomes, leading in turn to the spilling over of PSA-expressing exosomes in the blood of PCa patients.•The use of plasmatic PSA-exosomes may be a novel, non-invasive clinical tool for screening and early diagnosis of prostate cancer.